High CDKN2A/p16 and low FGFR3 expression predict progressive potential of stage pT1 urothelial bladder carcinoma - Breyer, Johannes; Erben, Philipp; Worst, Thomas (Clinical genitourinary cancer, 2018)
Background - A recent study on the comprehensive genomic profile of advanced urothelial bladder cancer (UBC) showed cyclin-dependent kinase inhibitor 2A (CDKN2A) and fibroblast growth factor receptor 3 (FGFR3) as the most often clinically relevant genomic alterations. Therefore, the prognostic role of FGFR3 and CDKN2A/p16 for pT1 UBC was studied. - Patients and Methods - Clinical data and formalin-fixed paraffin-embedded tissues of pT1 UBC treated with an organ-preserving approach was analyzed retrospectively. Total RNA was isolated using commercial RNA extraction kits and mRNA expression of CDKN2A/p16 and FGFR3 was measured using single step reverse transcription quantitative real time polymerase chain reaction using RNA-specific TaqMan assays. - Results - Data from 296 patients (79.4% male; median age: 72 years) could be used for the final evaluation. Spearman correlation revealed a statistically significant negative correlation between mRNA expression of CDKN2A/p16 and FGFR3. There was a positive correlation between CDKN2A/p16 and G3 tumors (ρ = 0.1875; P = .0012) and associated carcinoma in situ (ρ = 0.1703, P = .0033) and a negative correlation between FGFR3 and these factors (ρ = −0.2791, P < .0001 and ρ = −0.2182, P = .0002). High CDKN2A/p16 expression (≥38.04) and low FGFR3 expression (<39.14) were statistically significantly associated with worse progression-free survival (PFS; P = .0194 and P = .0089). Multivariate Cox regression analysis could identify patients with low FGFR3 and high CDKN2A/p16 expression (log rank (LR) χ2 = 10.69; P = .0048) as well as tumor size ≥3 cm (LR χ2 = 6.03; P = .0141) as independent predictors for PFS. - Conclusion - High expression of CDKN2A/p16 and low expression of FGFR3 show a correlation with established prognostic features for non–muscle-invasive bladder cancer and can predict progression of stage pT1 UBC.
Gesehen am 15.08.2019